Antioxidant and Anti-Inflammatory Capacities of Fractions and Constituents from Vicia tetrasperma - Duc Dat Le; Kyung Hyun Min; Mina Lee (MDPI AG, 2023)
The young leaves and shoots of V. tetrasperma are consumed daily as cooked vegetables and can provide various health benefits. The antioxidant and anti-inflammatory capacities of its total extract and fractions were accessed for the first time in this study. The bioactivities guided the separation of the active fraction (EtOAc), leading to the identification of nine flavonoid glycoside compositions from this plant for the first time. In addition, the fractions and all isolates were evaluated for their inhibition against NO and IL-8 production in LPS-stimulated RAW264.7 and HT-29 cell lines, respectively. The most active ingredient was further assayed for its inhibitory abilities to iNOS and COX-2 proteins. Indeed, its mechanisms of action modes were confirmed by Western blotting assays through the reduction in their expression levels. An in silico approach revealed the substantial binding energies of docked compounds into established complexes to verify their anti-inflammatory properties. In addition, the presence of active components in the plant was validated by an established method on the UPLC-DAD system. Our research has boosted the value of this vegetable's daily use and provided a therapeutic approach for the development of functional food products for health improvement regarding the treatment of oxidation and inflammation.